Modeling of pressure-volume controlled artificial respiration with local derivatives - Acay, Bahar; İnç, Mustafa; Chu, Yu-Ming; Almohsen, Bandar (Springer, 2021)
We attempt to motivate utilization of some local derivatives of arbitrary orders in clinical medicine. For this purpose, we provide two efficient solution methods for various problems that occur in nature by employing the local proportional derivative defined by the proportional derivative (PD) controller. Under some necessary assumptions, a detailed exposition of the instantaneous volume in a lung is furnished by conformable derivative and such modified conformable derivatives as truncated M-derivative and proportional derivative. Moreover, we wish to investigate the performance of the above-mentioned operators in applications by plotting several graphs of the governing equations.
Keywords: Proportional derivative; Local derivatives; Clinical medicine; Truncated M-derivative; Conformable derivative